Network analysis of submarine canyon seascape : implications for planning and biodiversity management - Matos, Fábio Emanuel Lopes de (2018)
Submarine canyons are complex and heterogeneous geomorphologic structures highly relevant for the biodiversity and productivity of continental margins. These marine ecosystems play a key role providing invaluable goods and services for human well-being but are also increasingly subjected to the effects of anthropogenic pressure and climate change. The natural isolation of canyons may act synergistically with these changes with implications for population connectivity and the maintenance of biodiversity. The understanding of the causes and ecological consequences of such changes requires holistic and interdisciplinary approaches. I mapped the landscape of submarine canyon research based on a comprehensive bibliographic data set and using data mining techniques and network analysis. The existing knowledge clusters, historical trends, emergent topics and knowledge gaps in canyon research were identified and characterized. Topics such as “Geology & Geophysics”, “Oceanographic Processes” and “Biology & Ecology” were among the most studied while, for instance, “Biogeochemistry” and ecological modelling were among the less explored. Topics regarding anthropogenic impacts and climate-driven processes were only detected on publication of the last decade. The knowledge network reflects a latent interdisciplinarity in canyon research that developed mostly in the new millennium, supported by a well implemented and international collaboration network. The research efforts have been mainly directed towards only a few canyon systems and a thematic bias was identified, with specific topics addressed preferentially in particular canyons. This spatial and thematic bias, together with the paucity of truly inter-disciplinary studies, may be the most important limitation to the integrated knowledge and development of canyon research and hinders a global, more comprehensive understanding of canyon patterns and processes. The scientific landscape mapping and the complementary results are made available online as an open and interactive platform. In order to assess the importance of submarine canyons for the conservation and management on the deep sea, a study area and a modelling species were selected: the Mediterranean Sea and Lophelia pertusa, a cold-water coral species. The Mediterranean Sea encompasses several submarine canyon systems and L. pertusa is an ecosystem engineering species that occurs frequently in these geomorphological features and provides refuge, nursery grounds and physical support for a remarkable diversity of other life forms. Considering that the distribution of L. pertusa in the Mediterranean Sea is probably underestimated and that this information is crucial to assess the relevance of canyons in the Mediterranean seascape, I estimated the habitat suitability and draw uncertainty maps for this region based on environmental predictors and an ensemble approach of three machine-learning algorithms. The results suggest that in the Mediterranean Sea, L. pertusa encounters environmental settings close to its physiological limits but, despite the highly variable quality of the seascape, submarine canyons were identified as high suitability areas, especially across the Western and Central Mediterranean margins. In addition to the environmental suitability, the ecosystem connectivity determines the species distribution, the metapopulation dynamics and population resilience. I simulated the transport of L. pertusa larvae in the Mediterranean Sea using a biophysical model to estimate their potential dispersal as well as a network analysis to evaluate the habitat availability based on parameters such as suitability, spatial configuration of the seascape and the oceanographic conditions variability. The results suggest that connectivity among Mediterranean ecoregions is weak and that the intensification of climate-driven events (e.g., dense shelf water cascading) may worsen this scenario. However, the potential exchange of larvae between colonies within the same ecoregion was significant, favoring population resilience to local disturbances. Habitat areas with high quality and larval flux were identified as a priority for the conservation of L. pertusa, and subsequently also for their associated fauna. Once again, I showed that habitat areas on submarine canyons may play an important role in the connectivity of L. pertusa Mediterranean populations. However, these habitat areas are subjected to intense anthropogenic pressures, which allied to the effects of climate change, may impose greater challenges to their conservation. Apart from three French marine protected areas in the Gulf of Lion, the development of conservation efforts considering submarine canyon in the Mediterranean Sea is negligible. The knowledge produced in this thesis provides scientific evidence to support decision-making in conservation and planning of marine protected areas networks in the Mediterranean Sea and illustrates the relevance of submarine canyon for the management and conservation of deep-sea biodiversity.